If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -17 = 8y + 1 Reorder the terms: -17 + 11y = 8y + 1 Reorder the terms: -17 + 11y = 1 + 8y Solving -17 + 11y = 1 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -17 + 11y + -8y = 1 + 8y + -8y Combine like terms: 11y + -8y = 3y -17 + 3y = 1 + 8y + -8y Combine like terms: 8y + -8y = 0 -17 + 3y = 1 + 0 -17 + 3y = 1 Add '17' to each side of the equation. -17 + 17 + 3y = 1 + 17 Combine like terms: -17 + 17 = 0 0 + 3y = 1 + 17 3y = 1 + 17 Combine like terms: 1 + 17 = 18 3y = 18 Divide each side by '3'. y = 6 Simplifying y = 6
| -2(4u-y)-2(-3y+u)= | | -(4y+1)-(-3y-5)=3 | | 4x^4+2x^3+x^2=0 | | 4(v+1)-7=3(v-1)+v | | x-38=-36 | | 8+4y-5=7y+10-2y | | 8=-6x-4 | | 18x^2-48xy+32y^2=0 | | 8x+9x=153 | | -9.7=4.7+y | | 36y^2-60y+25=0 | | -9(3b+2)+(28b-4)=0 | | 3.1q-2.2-3.7q=-1.6q-1.6 | | -(-v+x)+2(-4x-5v)= | | n-35=-44 | | 8-8y=2y+7878 | | -(8y+2)-(-7y-7)=2 | | 3(n-2)-1=2-5(n+5) | | 52=(4x+1)(x+1) | | 26+x+x+3x-34=692 | | LOG(5X-1)+LOG(X+3)=1 | | 6(4x-3)=3(8x+7) | | 6(4-3)=3(8x+7) | | 5x^4+4x^3-114x^2+36x+405=0 | | 2x(x+3)=(3x+1)(x+3) | | 7+8x-4=7x+39-3x | | (2x-7)(3x^2+7x+4)=0 | | 5r+6r=77 | | 5y^2-21y=0 | | 16r^3-9r=0 | | -2x^2+12x-13=0 | | 2x-16=x+36 |